FAKTOR-FAKTOR YANG MEMPEGARUHI PENDAPATAN PEDAGANG DI PASAR GULINGAN KECAMATAN MENGWI KABUPATEN BADUNG - I GUSTI AYU LIA YASMITA (GANEC SWARA, 2021)
The purpose of this study was to determine the effect of capital and working hours either partially or simultaneously on the income of traders in Gulingan Market, Mengwi District, Badung Regency. This research was conducted in Gulingan Market with a total sample of 80 respondents. The method used in this research is census technique. Data collection was carried out by interview, observation and documentation methods. The data analysis techniques used to solve the problems in this study were: 1) Classical Assumption Test which includes: Multicollinearity Test, Heteroscedasticity Test and Autocorrelation Test. 2) Hypothesis Testing using Multiple Linear Regression Analysis Techniques.      The results showed that capital and working hours simultaneously had a significant effect on the income of traders in Gulingan Market, Mengwi District, Badung Regency. Capital and working hours partially have a positive and significant effect on the income of traders in Gulingan Market, Mengwi District, Badung Regency.